Finding Hamiltonian cycles of truncated rectangular grid graphs in linear time - Keshavarz-Kohjerdi, Fatemeh; Bagheri, Alireza (Applied mathematics and computation, 2023)
•In this paper, we consider the problem of finding a Hamiltonian cycle for truncated rectangular grid graphs.•The necessary conditions for these graphs to be Hamiltonian are given and a linear-time algorithm to find a Hamiltonian cycle, if there exists, is presented.•The Hamiltonian cycle problem for solid grid graphs has been solved already in time O(n4) but we solved it in less time complexity for truncated rectangular grid graphs. The Hamiltonian cycle problem is an important problem in graph theory. For solid grid graphs, an O(n4)-time algorithm has been given. In this paper, we solve the problem for a special class of solid grid graphs, i.e. truncated rectangular grid graphs, in linear time.